Anna, Banana, and the sleepover secret - Rissi, Anica Mrose (Rissi, Anica Mrose. Anna, Banana, 2018)
"Anna and Sadie are excited to sleepover at Isabel's for the first time, but when a game of Truth or Dare goes wrong, they're left with a horrible secret"--